Compressive Behavior of Reconstituted Soils at High Initial Water Content: Case Study on South-Western Region Of Bangladesh - Riyad, A S M; Rafizul, Islam M; Kadir, Rezwana (Journal of Engineering Science, 2023)
This study illustrates the experimental investigation of the effect of high initial water content on the compression behavior of reconstituted soil. For this attempt, disturbed soil samples were collected from two selected locations of the KUET campus, Khulna, Bangladesh. The reconstituted soils were prepared in the laboratory at different initial water content, ranging from 0.7 to 1.2 times their corresponding liquid limit. The main focus of this study was to investigate the compression behavior of reconstituted clays using oedometer tests. This work was complementary to the intrinsic compression line concept proposed by Burland (1990). In the laboratory, ASTM methods were followed to measure the initial properties of soils. Here, it can be observed that e - logσv compression curves show an inverse "S" shape as a result of resisting deformation due to pressure. Moreover, some important correlations were developed based on the initial void ratio and the void ratio at the liquid Limit e0/eL . It has been observed that the void index is a dominating parameter to normalize the squeezability characteristics at different initial water contents in the plastic post-yield regime. A non-unique relationship is obtained for different soils to express the intrinsic compression line concept. However, there is a proportional relationship between intrinsic compressibility and initial water contents or liquid limits. Journal of Engineering Science 14(1), 2023, 1-9